Design and Development of Intelligent Aquaponics System - Khairi Mohd Zambri, Mohd; Shahrieel Mohd Aras, Mohd; Khamis, Alias; Nizam Mohd Shah, Hairol; Haniff Harun, Mohamad; Anas Yusof, Ahmad (International Journal of Engineering and Technology, 2018)
The aquaponics system is actually the integration system of two waste product. The aquaponics system can be ranged from the simple which is the fish tank is just below the plant bed to the more contemporary one where it using multiple of fish tanks and advance technology to maintain the water level, quality and pH of water and the interval time for the motor pump to be operated. To reduce the electrical energy consumption, the project carries out from the solar energy to make it more economical and safe. Furthermore, the system has many benefits. First, the crops are chemical-free as the nutrients from the fish acts as the fertilizer for the growing plant. The pH value of the water in fish tank will always persistent because of the circulating process. It also can be developed anywhere because it only requires a small space of area. Farmers can save the budget to spend on utility bills at the end of the month because the system applies renewable sources to generate energy. Lastly, aquaponics used minimal labor because man does not need to look after their grown crops for fertilizing, weeding or watering the plants.Â Â